Nanoscale control of competing interactions and geometrical frustration in a dipolar trident lattice. Issue 1 (December 2017) - Farhan, Alan; Petersen, Charlotte; Dhuey, Scott; Anghinolfi, Luca; Qin, Qi; Saccone, Michael; Velten, Sven; Wuth, Clemens; Gliga, Sebastian; Mellado, Paula; Alava, Mikko; Scholl, Andreas; et al.
Abstract Geometrical frustration occurs when entities in a system, subject to given lattice constraints, are hindered to simultaneously minimize their local interactions. In magnetism, systems incorporating geometrical frustration are fascinating, as their behavior is not only hard to predict, but also leads to the emergence of exotic states of matter. Here, we provide a first look into an artificial frustrated system, the dipolar trident lattice, where the balance of competing interactions between nearest-neighbor magnetic moments can be directly controlled, thus allowing versatile tuning of geometrical frustration and manipulation of ground state configurations. Our findings not only provide the basis for future studies on the low-temperature physics of the dipolar trident lattice, but also demonstrate how this frustration-by-design concept can deliver magnetically frustrated metamaterials. Artificial magnetic nanostructures enable the study of competing frustrated interactions with more control over the system parameters than is possible in magnetic materials. Farhan et al. present a two-dimensional lattice geometry where the frustration can be controlled by tuning the unit cell parameters.